The Role of Digital Media in Crisis Management in the Private Sector in the Kingdom of Saudi Arabia (The International Journal of Educational Sciences and Arts, 2025)
Research Title: The Role of Digital Media in Crisis Management in the Private Sector in the Kingdom of Saudi Arabia. The study aimed to identify the role of digital media in crisis management in the Saudi private sector. The study seeks to identify how digital media tools—such as social media platforms, websites, and interactive applications—can be used to monitor, interact with, and handle crises, in terms of speed of response, information transparency, and internal and external communication strategies. The study adopted a descriptive analytical approach by reviewing previous literature and analyzing several real-life examples of crises experienced by the Saudi private sector in recent years. It concluded that digital media can be an effective tool in crisis management if employed within clear and integrated institutional communication plans, while emphasizing the importance of building specialized digital communication teams within institutions. The study recommends developing digital infrastructure, enhancing the skills of communication teams, and formulating proactive media policies capable of efficiently addressing future challenges.
Keywords: Digital Media; Crisis Management; Private Sector; Kingdom of Saudi Arabia